Removal of an Upper Third Molar from the Maxillary Sinus - Klinger de Souza Amorim; Vanessa Tavares da Silva; Rafael Soares da Cunha; Maria Luisa Silveira Souto; Carla Rocha São Mateus; Liane Maciel de Almeida Souza (Hindawi Limited, 2015)
The maxillary sinus or antrum is the largest of the paranasal sinuses. It is located in the maxillary bone and has a proximity to the apexes of upper molars and premolars, which allows it to form a direct link between the sinus and the oral cavity. Dislocation of a foreign body or tooth to the interior of a paranasal sinus is a situation that can occur as a result of car accidents, firearm attacks, or iatrogenic in surgical procedures. Therefore, it is necessary to know how to treat this kind of situation. This study's objective is to report the case of a 23-year-old female patient, leucoderma, who sought treatment from the Surgical Unit at the Dental Faculty of the Federal University of Sergipe. She had a history of pain and edema in the right side of the genian region and two failed attempts at removing dental unit (DU) 18. The extraoral clinical exam revealed intense edema of the left hemiface with signs of infection, excoriation of the labial commissure, hematoma, a body temperature of 39°C, and a limited ability to open her mouth. The patient was medicated and treated surgically. The tooth was removed from the maxillary sinus with caution, as should have been done initially.